Viscosity effect on the spreading of PDMS over different solid substrates. (8th June 2010) - Alteraifi, Abdullatif M.; Herbawi, Abdel Hafiz; Chebbi, Rachid
This work examines the effect of viscosity as well as the role played by the solid substrate on the spreading kinetics of Polydimethylsiloxanes (PDMS) droplets. In the set of experiments, spreading of PDMS liquids with various viscosities (100 cP, 500 cP, 1000 cP, 10, 000 cP) was tested on three different solid substrates (glass, polymethylmethacrylate (PMMA) and polystyrene (PS)). For high viscosities (PDMS-1000 and PDMS-10, 000), the spreading data are found to be nearly independent of the substrates considered. The experimental results are compared with capillary spreading models not based on any fitting parameter. Chebbi model (2000) is found to have a good agreement, extending beyond the lubrication theory range, with the spreading kinetics data on the three solids for 500 cP, 1000 cP and 10, 000 cP viscosities. Overall, the model of Diez et al. (1994) presents larger deviations. In the 100 cP viscosity case, gravity effects come into play and systematic and increasing deviations with time are observed with both Chebbi and Diez et al. models as expected since gravity effects are omitted in both models.